AS VARIAÇÕES MENSAIS DA CESTA BÁSICA REGIONAL E O COMPORTAMENTO DA INFLAÇÃO - BRUM, ARGEMIRO L.; SOUZA, JOSÉ D. S. D.; DIDOLICH, EVERTON F.; RONCATTO, DAIANA; PETRY, DÉBORA; SAUGO, DIEGO A.; BRAUN, FELIPE A.; KUNZ, JULIANE; ZINGLER, KARINE D.; WILDNER, MARLUCI C.; et al. (Salão do Conhecimento, 2013)
Resumo